Peak running, mechanical, and physiological demands of professional men`s field hockey matches - Lin, L.; Ji, X.; Zhang, L.; Weng, H.; Wang, X. (Journal of Human Kinetics, 2023)
The aim of this study was to investigate the peak running, mechanical, and physiological demands of players of different positions in professional men`s field hockey matches. Eighteen professional male field hockey players participated in the study, and data were collected in eleven official matches. Players wore GPS units (Vector S7, Catapult Sports) and heart rate (HR) monitors (Polar H1, Polar Electros) to collect physical and physiological data. Physical and physiological output of forwards, midfielders, and defenders in full matches and during 1-min peak periods was analysed. For all metrics and positions, the values identified for the 1-min peak periods were greater than the average values of match play (p < 0.05). In terms of 1-min peak period Player Load, all three positions were significantly different from each other. Forwards achieved the highest Player Load per minute, while defenders the lowest. The distance per minute, high-speed distance per minute, and the relative average heart rate of defenders were significantly lower than of midfielders and forwards (p < 0.05). The current study revealed the peak running, mechanical, and physiological demands of professional men`s field hockey matches. It is recommended when prescribing training programmes, to consider not only match average demands, but also peak demands. Forwards and midfielders displayed similar peak demands, while defenders had the lowest demands in all metrics except the number of accelerations and decelerations per minute. Player Load per minute can be used to identify the differences in peak mechanical demands between forwards and midfielders